Criminal Sanctions for Domestic Violence: Analysis of Effectiveness and Victim Protection - Setiawan, Rahmat; Ogotan, Arianti A.; Mustikowati, Endang (Ipso Jure, 2025)
This study analyzes the effectiveness of criminal sanctions against perpetrators of domestic violence and the level of legal protection provided to victims based on Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law). The approach used is a normative juridical method by examining relevant laws and regulations, doctrines, and judicial practices. The results of the study show that although the PKDRT Law has provided a strong legal basis in cracking down on perpetrators, its effectiveness is still weak due to structural constraints, patriarchal culture, and lack of victim perspective among law enforcement officials. Legal protection for victims is still formalistic and has not touched on the aspects of psychological and social recovery. Therefore, it is necessary to reconstruct the criminal law paradigm through a restorative justice approach that prioritizes the restoration of the dignity of victims, social reconciliation, and the prevention of repeated violence. Reformulation of norms and strengthening the capacity of law enforcement agencies is also an urgent need for the law to function as an instrument of substantive justice, not just a tool of punishment. This research emphasizes that justice in domestic violence cases must be realized through a balance between legal certainty, victim protection, and universal human values.